Fabrication of spintronics device by direct synthesis of single-walled carbon nanotubes from ferromagnetic electrodes - Mohamed, Mohd Ambri; Inami, Nobuhito; Shikoh, Eiji; Yamamoto, Yoshiyuki; Hori, Hidenobu; Fujiwara, Akihiko (Institute of Physics Publishing, 2008)
We describe an alternative method for realizing a carbon nanotube spin field-effect transistor device by the direct synthesis of single-walled carbon nanotubes (SWNTs) on substrates by alcohol catalytic chemical vapor deposition. We observed hysteretic magnetoresistance (MR) at low temperatures due to spin-dependent transport. In these devices, the maximum ratio in resistance variation of MR was found to be 1.8%. © 2008 National Institute for Materials Science.